85 Conception Rates in Beef Cattle Inseminated with Either Sexedultra™ Sex-Sorted Semen or Conventional Semen after Estrus Is Synchronized for Fixed Time Artificial Insemination Using 7-Day Co-Synch. (1st March 2018) - Crites, B R; Vishwanath, R; Arnett, A M; Bridges, P; Burris, W R; McLeod, K R; Anderson, L
Abstract: The objective of this study was to compare conception rates of female beef cattle inseminated at a fixed-time with either conventional (CON ) or SexedULTRA™ sex-sorted (SU ) semen. Treatments included CON or SU with two sires represented within each treatment. Cows (n=316) and heifers (n=78) from six locations were randomly assigned treatment. Estrus was synchronized in all females using the industry-standard 7-d CO-Synch + controlled internal drug release (CIDR ) protocol (gonadorelin (GnRH; 100 μg i.m., Factrel) + CIDR [1.38 g progesterone] on d 0, dinoprost tromethamine (PG; 25 mg i.m., Lutalyse) at CIDR removal on d 7, and 100 μg GnRH on d 10, 54 h (heifers) or 66 h (cows) after CIDR removal). Estrotect™ estrous detection aids were applied at CIDR removal and estrous expression was recorded at insemination. Animals were assumed estrual if greater than 50% of the patch coating was removed. Conception rates to fixed-time artificial insemination (FTAI ) were analyzed using PROC GLIMMIX in SAS 9.4 and significance was determined at p <0.05. The results from this study indicated no main effects of treatment ( P= 0.34 ), location ( P=0.79 ), sire ( P= 0.65 ), or age ( P=0.8 ) on AI conception rates. However, a significant sire by treatment interaction was observed ( p=0.05 ). Conception rates were similar ( p=0.43 ) between CON (56.4%) and SU (54.8%) for Sire A, while conception rates with SU (44.9%) were lower ( p<0.05 ) compared to CON (59.6%) for Sire B. Conception rates did not differ ( p=0.25 ) between sires for CON (56.4% vs 59.6%), however, rates tended to differ ( p=0.09 ) for SU between Sire A (54.8%) and Sire B (44.9%). Conception rate for estrual females (62.8%) was higher ( p<0.0001 ) than non-estrual females (38.7%) at FTAI regardless of treatment. The interaction between estrous expression and treatment tended ( P=0.11 ) to impact conception rates. In the SU treatment, conception rates differed ( P<0.0001 ) between estrual (63.8%) and non-estrual females (27.3%). In contrast, no differences ( P=0.8 ) were observed between CON (61.9%) and SU (63.8%) in estrual females. Larger studies are warranted to determine appropriate timing of insemination with sex-sorted semen in FTAI protocols.